A new species, Stemonitis sichuanensis, and a newly recorded species, Stemonitis marjana (Myxogastria) from China - Bo, Zhang; Yu, Li (Phytotaxa, 2016)
A new species, Stemonitis sichuanensis, collected in Gexigou National Natural Reserve, Sichuan province, China, is described herein. This new species has a columella that usually ends in an ovoid to triangular expansion at the apex of the sporotheca and small spores (about 6–7 μm in diam.). We present a scanning electron micrograph study of S. sichuanensis and a key to the species in the genus Stemonitis. Holotype specimens of S. sichuanensis are deposited in the Herbarium of the Mycological Institute of Jilin Agricultural University (HMJAU), Changchun, China. We also report a new record of another species of Stemonitis, S. marjana Y. Yamam., in this paper, specimens of which are also deposited in the HMJAU.